Leverage decisions and manager characteristics: Evidence for european banks - Cerejeira, João (2022)
This study assesses how manager’s characteristics influence leverage decisions. Using data from European banks, the results show that younger managers are riskprone and less conservative in leverage decisions. Moreover, it is observed that for higher levels of leverage more experienced managers tend to increase leverage. This is also true for managers with a longer tenure as they may bring their personal preferences towards risk. However, this effect differs according to the level of leverage at the manager’s appointment date. The inclusion of the decision horizon seems to validate the idea that a short-term managerial horizon enhances the selfinterested behaviour of the manager and this is reflected on capital structure decisions.